Development Of STEM-Based PjBL E-Student Worksheet to Foster Character Building - Retni S Budiarti; Harlis; Jodion Siburian (Postgraduate, University of Mataram, 2023)
This research aims to determine whether E-Student Worksheet for Project-Based Learning (PjBL) based on STEM (Science, Technology, Engineering, and Mathematics) can cultivate valid and practical Character Building for microbiology learning. This type of research falls under Research and Development (R&D). The study employs the 4D research model (Four D models), adapted from Thiagarajan (as cited in Kurniawan et al., 2017). The 4D development consists of four stages: Define, Design, Development, and Disseminate. Instruments used include media expert validation sheets, content expert validation sheets, and practicality sheets for students. The data obtained are analyzed descriptively, both quantitatively and qualitatively. The feasibility of the STEM-based PjBL e-Worksheet for Character Building development is validated with a media validity of 91.67% and content validity of 88.89%, meeting the criteria for being highly valid. Therefore, it can be tested on students of Biology Education at the Faculty of Teacher Training and Education, University of Jambi. Practicality, as assessed by student responses using STEM-based PjBL learning media, is 90.83%, meeting the criteria for being highly practical. In conclusion, the development of STEM-based PjBL e-Worksheet demonstrates tremendous potential in shaping students' character while enhancing their academic abilities. The integration of technology and project-based learning approaches creates interactive and contextual learning experiences, preparing students for the technological challenges of the workforce.